The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1103/physrevb.93.184430
|View full text |Cite
|
Sign up to set email alerts
|

Negative exchange bias in single-phaseDy1xNdxCrO3

Abstract: Observation of significant negative exchange bias (H E ) is reported in solid-solutions of single phase samples of Dy 1-x Nd x CrO 3 for x = 0.33, 0.67, and 1 with the corresponding Néel temperatures at = 175 K, 200 K, and 225 K respectively, and the spin-reorientation transitions T SR at 48 K, 58 K, and 38 K respectively. In contrast, no H E was observed for the sample with x = 0 (i.e. DyCrO 3 ) shows no H E below its = 145 K and no reorientation of spins at lower temperatures was observed. More importantly, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…480 cm −1 (for DyCrO 3 ) and 470 cm −1 (for HoCrO 3 ) are the superposition of a B 3g mode from out-ofphase O 2 scissor-like phonons, an A g mode from CrO 6 bending, and a B 2g mode from CrO 6 out-of-phase bending. 25 Thus, the Raman spectra of DyCrO 3 and HoCrO 3 show the characteristic vibration behavior of these two samples.…”
Section: Resultsmentioning
confidence: 86%
“…480 cm −1 (for DyCrO 3 ) and 470 cm −1 (for HoCrO 3 ) are the superposition of a B 3g mode from out-ofphase O 2 scissor-like phonons, an A g mode from CrO 6 bending, and a B 2g mode from CrO 6 out-of-phase bending. 25 Thus, the Raman spectra of DyCrO 3 and HoCrO 3 show the characteristic vibration behavior of these two samples.…”
Section: Resultsmentioning
confidence: 86%
“…The magnetization reversal with the positive and negative EB in perovskite chromite YbCrO 3 is obtained due to the competing interaction between the FM component of Cr 3+ and Yb 3+ moments [10] . The EB behavior without any magnetization reversal has been reported for rare-earth-doped orthochromite Dy 1−x Nd x CrO 3 [11]. The EB effect is also observed from horizontal and vertical shifts from the origin in field-cooled magnetization hysteresis loops in weak ferrimagnet LuFe 0.5 Cr 0.5 O 3 [12].…”
Section: Introductionmentioning
confidence: 65%
“…Initially, such negative EB at 30 K for low cooling fields was reported in isostructural NdMnO 3 [9]. Also, the only negative H EB has obtained for Dy 1−x Nd x CrO 3 shows the EB effect without any magnetic reversal [11]. around T * ∼ 90 K. To analyze the T window of having maximum H EB (T) and the concurrent minima of H C (T ), the field ratio H EB /H C , as the function of T is plotted in figure 8(c).…”
Section: Magnetic Propertiesmentioning
confidence: 86%
“…Experimental studies by McDannald et al reported reduction in T N 1 (145 K → 140 K) and lowest asymmetric (1.9 K)/symmetric (9.35 K) magnetic exchange interactions in Er substituted DyCrO 3 polycrystals [23]. While the Nd substituted DyCrO 3 polycrystals exhibit a large negative exchange bias (H eb ∼ −2212 Oe) between the AFM ordering temperature and spin-reorientation transitions within the canted Γ 7,Cr phase where a progressively increasing trend has been noticed in the H eb with increase in the Nd substitution at Dy sites [27,28]. It is interesting to note that the mixed perovskites such as orthochromite-orthoferrite RFe 0.5 Cr 0.5 O 3 (R = Tb, Dy, Ho, Er) exhibits metamagnetic like transitions across 7 kOe along with spin reorientation transitions [29].…”
Section: Introductionmentioning
confidence: 98%